2021
DOI: 10.2147/ppa.s324315
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Thresholds of Minimum Necessary Adherence for Effective Treatment with Direct Oral Anticoagulants – A Retrospective Cohort Study in Health Insurance Claims Data

Abstract: Background An essential contribution regarding the prevention of thromboembolic events in patients with (non-valvular) atrial fibrillation (AF) is good adherence to direct oral anticoagulants (DOACs). However, it is an open question what “good” adherence means for DOACs or below which threshold non-adherence is clinically relevant for AF patients. Ultimately, such a classification could prevent strokes and associated costs through adjusted treatment regimens or supportive measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…Aiming for a high adherence to anticoagulants is crucial, as recent studies have shown that the risk of adverse outcomes was lowest in patients with a PDC of ≥ 90% ( 7 , 8 ). Although the observed high adherence to NOACs is in line with previous literature ( 6 , 8 , 10 , 12 , 24 , 34 , 41 ), results on differences in adherence to individual NOACs are more conflicting, with some studies ( 6 , 13 , 24 , 34 ) favoring adherence to once-daily dosed NOACs, whereas other studies ( 7 , 10 , 30 ) described a higher adherence to twice-daily dosed apixaban. However, missing one dose of twice-daily dosed NOACs may not result in a comparably reduced thromboembolic protection as missing one dose of once-daily dosed NOACs, especially since once-daily dosed rivaroxaban and edoxaban actually have the shortest half-lives of NOACs ( 6 , 24 , 46 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Aiming for a high adherence to anticoagulants is crucial, as recent studies have shown that the risk of adverse outcomes was lowest in patients with a PDC of ≥ 90% ( 7 , 8 ). Although the observed high adherence to NOACs is in line with previous literature ( 6 , 8 , 10 , 12 , 24 , 34 , 41 ), results on differences in adherence to individual NOACs are more conflicting, with some studies ( 6 , 13 , 24 , 34 ) favoring adherence to once-daily dosed NOACs, whereas other studies ( 7 , 10 , 30 ) described a higher adherence to twice-daily dosed apixaban. However, missing one dose of twice-daily dosed NOACs may not result in a comparably reduced thromboembolic protection as missing one dose of once-daily dosed NOACs, especially since once-daily dosed rivaroxaban and edoxaban actually have the shortest half-lives of NOACs ( 6 , 24 , 46 ).…”
Section: Discussionsupporting
confidence: 88%
“…The PDC was calculated as the number of days covered with NOAC supply during a time interval, divided by the total number of days of that time interval (PDC range 0–100%). In order to specifically investigate patient-related NOAC adherence at home, only ambulatory prescription claims were considered, consistent with previous studies ( 7 , 10 , 12 ). In case of hospitalization, the length of inpatient stay was deducted from the number of days in the studied time interval ( 7 , 10 , 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis thus built on already processed data (described in detail elsewhere). 24 In brief, DOAC-naive patients with AF who newly initiated either rivaroxaban or apixaban treatment were followed up from their first DOAC prescription if they met the inclusion criterion of at least 3 follow-up prescriptions and had no exclusion criterion in their medical history. Supplementary Figure S1 depicts the flow of participants and how the study cohort was defined by inclusion and exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%